10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
HIV stigma remains a stubborn barrier to antiretroviral therapy (ART) adherence and interventions to improve ART adherence are not well-informed by stigma mechanisms. Stigma theories posit that past stigma experiences sensitize individuals to anticipate future stigma. Furthermore, the impact of anticipated stigma on ART adherence may be explained by stigma-induced distress and behaviors to avoid future stigma. Grounded in contemporary stigma theories, the current study examined stigma-induced distress and stigma avoidance behaviors as serial mediators in the association between anticipated stigma and ART adherence. People living with HIV and receiving ART (N = 695) were enrolled in a 1-month prospective study. We confirmed our main hypothesis that stigma-induced distress was associated with stigma-avoidance behaviors, and that distress and avoidance serially mediated the association between anticipated stigma and ART adherence. We conclude that stigma-induced distress and stigma-avoidance strategies are amenable targets for behavioral interventions to reduce the impacts of stigma on adherence.